HIV Tat protein affects circadian rhythmicity by interfering with the circadian system. Issue 9 (20th April 2014) - Wang, T; Jiang, Z; Hou, W; Li, Z; Cheng, S; Green, LA; Wang, Y; Wen, X; Cai, L; Clauss, M; Wang, Z
<x xml:space="preserve">Abstract</x> Objectives Sleep disorders are common in patients with HIV/AIDS, and can lead to poor quality of life. Although many studies have investigated the aetiology of these disorders, it is still unclear whether impaired sleep quality is associated with HIV itself, social problems, or side effects of antiretroviral therapy (ART). Moreover, despite its known neurological associations, little is known about the role of the trans‐activator of transcription (Tat) protein in sleep disorders in patients with HIV/AIDS. The purpose of this study was to test the hypothesis that the sleep quality of patients with HIV/AIDS affected by an altered circadian rhythm correlates with cerebrospinal HIV Tat protein concentration. Methods Ninety‐six patients with HIV/AIDS between 20 and 69 years old completed the Pittsburgh Sleep Quality Index. Their circadian rhythm parameters of blood pressure, Tat concentration in cerebrospinal fluid, melatonin concentration, CD4 cell count and HIV RNA viral load in serum were measured. Results The circadian amplitude of systolic blood pressure and the score for sleep quality (Pittsburgh Sleep Quality Index) were negatively correlated with HIV Tat protein concentration, while the melatonin value was positively correlated with Tat protein concentration. Conclusions The HIV Tat protein affects circadian rhythmicity by interfering with the circadian system in patients with HIV/AIDS and further increases the melatonin excretion value. A Tat protein‐related high melatonin value may counteract HIV‐related poor sleep quality during the progression of HIV infection. This study provides the first clinical evidence offering an explanation for why sleep quality did not show an association with progression of HIV infection in previous studies.